To eliminate icing and condensation in temperature cycling chambers - Ramalingam, Premnathan (2017)
In reliability testing,the temperature cycle chamber is one of the most common pieces of equipment needed to assess semiconductor devices reliability.Temperature cycling involves subjecting the semiconductor devices to an environment test to hot and cold temperature cyclic transition.In a temperature cycling stress which were needed to run for a longer period (higher number of cycles request),ice induced in the cold zone and this icing have been a long lasting unsettled issue.In Reliabi lity Product Test lab (RPT) of Infineon Technologies Melaka there are total of 16 dual zone air-to-air temperature-cycling chambers.There are various values of temperatures requested to run,where cycles start from 80°C to 175°C (in the hot zone) and from -35°C to -65°C (in the cold zone).Icing in cold zone has been one of the main reasons for various problems occurred which not only effecting the chamber itself but also effects the whole temperature cycling stress test.Some of the problems are such as cradle basket jammed,spindle shaft bend,blower fan motor propeller damage,cradle motor damage,pneumatic cylinder jammed or spoil etc.Icing also cause the cooling to be slow which directly will cause the cycling process to be slow and this will affect the overall temperature cycling stress cycle time.There are multiple studies and physical trials have been conducted to solve this icing issue for quit sometime.The icing only can be eliminated if the wet molecules are removed from the chamber.As suggested by some chamber manufacturers,compressed dry air is the first choice but it is not effective for longer running processes.In this research,the trials using dry air also conducted.Finally after gone through some trials,go through online articles and discussion with the chamber manufacturers,a better solution was justified.That is by purging N2 gas into temperature cycl ing chambers.Like compressed dry air,N2 also will remove the wet molecules but it will be faster and will be suitable for longer running processes.The N2 gas will be purged into both hot and cold zone in an optimum volume. In this research,the optimum volume was identified.Result from the research will be shared to the management of Infineon Technologies RPT Lab for improvement actions implementation.